Vending environment and hygiene practices of street food vendors in an out of campus food environment in Kenya - Gichunge, Catherine; Ogachi, Solomon; Kiboi, Willy; Mukhwana, Eugine S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Street foods (SF) are ready-to-eat foods and the safety and hygiene practices of street food vendors (SFVs) are important in the prevention of food-borne diseases (FBD). This study assessed the food handling practices and vending environments of SFVs operating outside a public university (Chuka University) in Ndagani, Kenya. Methods: The study used an observational cross-sectional design where SFVs were observed during data collection. Census sampling was used to recruit 100 SFVs in Ndagani, Kenya. The collected data were summarized using frequencies and percentages. Chi square and regression analysis were used to assess the association and relationship between the SFVs’ demographic characteristic (sex) and their food handling practices and vending environment. Statistical significance was set at p≤0.05. Results: Of the 100 SFVS who participated in the study 87% (n=87) were female. Only 10% (n=10) of the SFVs were vending in a sanitary environment while 88% (n=88) of the SFVs had sub-optimal food handling practices. There was an association between the SFVs sex and vending environment (p=0.003) and their food handling practices (p=0.008). Compared to male SVFs, female SFVs were 10.1 times more likely to vend in an unsanitary environment (OR: 10.1; C.I, 2.41-42.60, p=0.002) and 7.1 times more likely to have sub-optimal food handling practices (OR: 7.1; C.I, 1.84-27.79, p=0.005). Conclusions: The majority of SFVs are working in unsanitary environments and not handling SFs safely and hygienically. SFVs need training on food safety to prevent an outbreak of FBD within the university community.